Allocating airport slots: The history of early applied experimental research - Andrej Svorenécík (Duke University, Center for the History of Political Economy (CHOPE), 2016)
The aviation industry changed dramatically in the wake of the Airline Deregulation Act of 1978. My paper looks at an element of this transformation - the policy according to which take off and landing slots were allocated at congested airports including a proposal to change this policy - an issue that affected millions of passengers annually. Caltech economists and experimentalists David Grether, Mark Isaac and Charles Plott were hired by the Civil Aviation Board to study the existing slot scheduling committees that used unanimity voting rule as well as alternative slot allocation mechanisms. I use their study to trace and depict the emerging practice of applied experimental research as a multilayered endeavor which involves an interplay among theoretical, empirical, and practical considerations (akin to economic modeling) that allows the experimenter to move from the naturally occurring phenomenon to its study in a laboratory only to return back with a policy recommendation. This demonstrates that applied experimental economics research went hand in hand with the emergence and rise of experimental economics in the 1980s.
Keywords: B21; B31; C91; D47; L93; 330; applied economics; experimental economics; airport slot allocation; airline regulation